CONSTRUCTION OF SIGNS AND MYTHS IN PRE-WEDDING PHOTOGRAPHY - Wahyu Lukito; Intan Rizky Mutiaz; Yasraf Amir Piliang (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2016)
In pre-wedding photograph there are visual signs those break conventional codes, then create unconventional concepts, which have potentials to create unconventional myth on pre-wedding photograph. The objectives of this research are to identify visual signs, unconventional codes and concepts on pre-wedding photograph. Through the observation toward some pre-wedding photograph samples those taken purposively base on have unconventional codes trend, analyze with photography semiotic toward pre-wedding photograph which uploaded in vendor's Instagram account within a certain period, describe unconventional code those create unconventional concepts which have potential to create unconventional myth on pre-wedding photograph. The unconventional codes created through breaking conventional codes process on them. The breaking process through modifies the visual signs, which not generally applied on pre-wedding photographs. And also the breaking process creates unconventional concepts on pre-wedding photograph, which have potential to create unconventional myth for long time to go.Â Keywords: Code, Myth, Pre-wedding, Photography, Sign